Changes in Optic Nerve Sheath Diameter in Response to Various Levels of End-Tidal Carbon Dioxide in Healthy Patients under General Anesthesia - Kapoor, Indu; Khandelwal, Ankur; Mahajan, Charu; Prabhakar, Hemanshu; Bithal, Parmod Kumar (Journal of Neuroanaesthesiology and Critical Care, 2018)
Background Intracranial pressure (ICP) monitoring is an essential component in management of traumatic brain-injured (TBI) patients. While invasive techniques are associated with many complications, noninvasive nature of ultrasonographic measurement of optic nerve sheath diameter (ONSD) is now becoming popular. Carbon dioxide (CO2) alters the ICP by changing the size of cerebral vasculature. We aimed to assess the effect of (hypercarbia and hypocarbia) different levels of end-tidal carbon dioxide (EtCO2) on ONSD.Methods Thirty adult patients aged between 18 and 65 years, undergoing brachial plexus injury surgery under general anesthesia, were enrolled. Following standard anesthetic protocol, ONSD was measured at different time points of EtCO2. ONSD was measured at EtCO2 of 40 and then 30 mm Hg to assess change in ONSD due to hypocarbia (Thypocarbia). Similarly, ONSD was measured at EtCO2 of 50 mm Hg to assess change in ONSD due to hypercarbia (Thypercarbia). The mean of three ONSD values at each time point was taken as the final value. The generalized estimating equation (GEE) was used to analyze correlation between different levels of EtCO2 and ONSD.Results The calculated 95% confidence interval (CI) for the difference of two measures (Thypocarbia, EtCO2 40 and 30 mm Hg) on ONSD was −0.056 to −0.036, and the calculated CI for the difference of other two measures (Thypercarbia, EtCO2 40 and 50 mm Hg) on ONSD was 0.044 to 0.077, and thus were observed to be significant.Conclusions ONSD changes significantly in response to different EtCO2 levels in healthy non-neurosurgical patients under general anesthesia.
Keywords: optic nerve sheath diameter; end-tidal carbon dioxide; intracranial pressure; hypocapnia; hypercapnia